[Sellar tumors] - Weber, M; Zoubaa, S; Politi, M; Grunwald, I; Essig, M (2007)
Because of the complex anatomy, examination of the sella turcica and hypophysis needs a dedicated MR sequence protocol. Not every sellar lesion is a pituitary adenoma. Thus, this review article summarizes the most frequently encountered intra-, supra-, and parasellar tumors and lesions. Differential diagnoses comprise besides adenoma among others craniopharyngioma, meningioma, glioma, germinoma, hamartoma, aneurysm, trigeminal schwannoma, pituitary carcinoma, chordoma, metastasis, infection, and empty sella. Characteristic imaging findings are presented and correlated to micro- and macro-pathology.